Implications for body weight extremes in solid organ transplantation. Issue 1 (19th January 2021) - Campara, Maya; Lourenco, Laura M.; Melaragno, Jennifer I.; Kaiser, Tiffany E.
Abstract: The pharmacokinetic profiles of medications are altered in overweight and underweight patients, but few studies have described these differences in patients with body mass index extremes. As solid organ transplant programs expand their candidate selection criteria to accommodate a growing population of patients with weight extremes, it has become imperative to understand and evaluate the impact weight extremes have on the pharmacokinetics of life‐sustaining immunosuppression in this population. This review will describe pharmacokinetic and dosing considerations for weight extremes in solid organ transplant recipients, including changes following bariatric surgeries, non‐pharmacologic and pharmacologic management strategies for weight loss and gain, and potential drug‐drug interactions with popular weight management products.